A sociological analysis of the involvement of men in campaigns against sexual violence towards women at Rhodes University: the aftermath of the #RUReference protest - Roboji, Philasande Milisa (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
Gender-based violence more especially sexual violence towards women is one of the biggest social issus affecting South Africa including higher institutions of learning, universities in this context. In recent years, we have seen students in universities protesting sexual violence demanding universities to improve their ways of dealing with this violence. The motivation behind this thesis is the notion that sexual violence is a women's issue and how most men in our communities and universities do not involve themselves in campaigns that are designed to end sexual violence towards women. There is an assumption that women should be the ones fighting against sexual violence because it affects them when in fact sexual violence affects everyone and more importantly, is mostly perpetuated by men. Therefore, the main purpose of this thesis was to sociologically analyze the involvement of men in campaigns against sexual violence towards women and the aftermath of the #RUReferenceList protest that took place at Rhodes University in 2016. This protest started immediately after a list of students who were said to be alleged sexual perpetrators was published online. Attached to this primary objective, the sub-goals that informed the entire study were to investigate how the involvement of men in the #RUReferenceList protest has contributed to challenging rape culture at Rhodes University. Also, to investigate if there are any ongoing campaigns and/or projects that includes men and that are still addressing the issue of sexual violence towards women. There is however, a dearth of research on the involvement of men in campaigns against sexual violence in South Africa. Therefore, it was difficult finding existing literature that touches on the involvement of men in campaigns against sexual violence towards women particularly in the context of universities. This thesis was conducted within the premises of Rhodes University through a qualitative research approach in a form of in-depth interviews. Five participants were selected through purposive sampling which included the Chair of the Gender Action Forum, one former student representative council member, a sub-warden from a male residence and two students. The findings of this research are not the full representation of the entire university but opinions and perspective of the participants that were interviewed. Their opinions and perspectives have a potential of contributing to the factors and reasons as to why majority of men have not engaged themselves in issues of gender-based violence or involved themselves in campaigns against sexual violence towards women.
Keywords: #RUReferenceList; Rhodes University -- Students -- Attitudes; Rape in universities and colleges -- South Africa; Social movements -- South Africa -- Makhanda; Women college students -- Violence against -- South Africa; Male college students -- South Africa -- Attitudes